Effective Use of "Guest Lecturers" in Online Instruction - Rogers, Emily; Carrier, Howard S. (University of West Georgia Distance & Distributed Education Center, 2018)
“Guest lecturers” can share insight and experiences, especially in classes that support professional programs, but how can they be best utilized in the online teaching environment? In presenting this paper at DLA 2018, the authors seek to discuss this question, drawing upon their recent, empirical research investigating the role of guest lecturers in online library science classes.
Conference Proceedings, 2018 Distance Learning Administration Conference, Jekyll Island, Georgia, June 24-27, 2018.